2020
DOI: 10.1186/s40008-020-00227-z
|View full text |Cite
|
Sign up to set email alerts
|

An agribusiness perspective of demonetization in central region of the state of Gujarat in India

Abstract: This paper aims at understanding the effect of demonetization announced in November 2016 on agribusiness subsystems, its effect on consumer purchasing criteria, and the problems that surfaced in rural areas to move towards digitalization. This research was exploratory in nature and so adopted an open-ended approach through interviews of 200 farmers selected from 20 villages of two districts; one economically progressive and the other economically backward, in central region of the state of Gujarat in India. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The reports of RBI indicate that post-demonetization, there has been a sharp rise in the number of accounts (272,000 Million to 728,340 Million) under the Pradhan Mantri Jan Dhan Yojana (PMJDY) and a surge in digital transactions (RBI, 2017;Fouillet, Guérin & Servet, 2021;Jawed et al, 2019). However, Singh & Prajapati (2020) found that infrastructural bottlenecks (less availability of bank branches, agricultural credit society, and ATMs) were perceived as hindrances to encouraging digital transactions. Hence, there is a long way to promote digitalization catering to all small sections of Indian states.…”
Section: Demonetization: a Necessity Or Casualtymentioning
confidence: 99%
See 1 more Smart Citation
“…The reports of RBI indicate that post-demonetization, there has been a sharp rise in the number of accounts (272,000 Million to 728,340 Million) under the Pradhan Mantri Jan Dhan Yojana (PMJDY) and a surge in digital transactions (RBI, 2017;Fouillet, Guérin & Servet, 2021;Jawed et al, 2019). However, Singh & Prajapati (2020) found that infrastructural bottlenecks (less availability of bank branches, agricultural credit society, and ATMs) were perceived as hindrances to encouraging digital transactions. Hence, there is a long way to promote digitalization catering to all small sections of Indian states.…”
Section: Demonetization: a Necessity Or Casualtymentioning
confidence: 99%
“…On the other hand, some economists such as Paul Krugman, Manmohan Singh, Amartya Sen, P Chidambaram Kaushik Basu, Jean Dre`ze, Jayati Ghosh, Prabhat Patnaik, Arun Kumar, and Larry Summers did not consider this policy commendable (Jawed et al, 2019;Mohindra & Mukherjee, 2018). Singh & Prajapati (2020) Demonetization has been used worldwide as an effective tool to curb black money. It was used in economies where most economic activities were handled in high denomination bills (Lahiri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several foreign firms are attracting to the Indian food market; they collaborate with Indian firms to expand their business and look for development opportunities for themselves (Shah et al , 2020). The researcher suggested that foreign direct investment (FDI) growth is driven by introducing reform in business such as the simple approval process of various licenses, open restricted sector for foreign investors and transparent tax administration system (Singh and Prajapati, 2020). With time, agribusiness marketing and trade dynamics have changed immensely over the years; however, the extent of change that agribusiness has seen over the years has not been able to match the desired level in countries such as India, China and Pakistan, especially (McMichael, 2020; Rehman et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%